Deletion of the serotonin transporter perturbs BDNF signaling in the central amygdala following long-access cocaine self-administration. (1st December 2019) - Caffino, Lucia; Mottarlini, Francesca; Diniz, Danielle Mendes; Verheij, Michel M.; Fumagalli, Fabio; Homberg, Judith R.
Highlights: Cocaine self-administration decreases BDNF levels in amygdala of wild-type rats. This decrease in BDNF levels upregulates TrkB-Akt-ERK1 signaling. Cocaine-induced changes are copied in naïve serotonin transporter knockout rats. Cocaine decouples BDNF and TrkB-AKt-ERK1 signaling in the knockout rats. Abstract: Background: Human neuroimaging studies indicate that the amygdala plays a key role in cocaine addiction. One key plasticity factor that modulates effects of cocaine on the brain is Brain-Derived Neurotrophic Factor (BDNF). A wealth of evidence shows that cocaine exposure alters BDNF signaling in corticolimbic structures, but, surprisingly, such evidence is very limited for the amygdala. Additionally, while BDNF is strongly regulated by serotonin levels and inherited serotonin transporter down-regulation is associated with increased vulnerability to cocaine addiction, the effects of serotonin transporter genotype on BDNF signaling in the amygdala under naïve and cocaine exposure conditions are unknown. Methods: We measured BDNF signaling in the central amygdala of wild-type and serotonin transporter knockout rats 24 h into withdrawal from long-access cocaine self-administration. Results: In wild-type rats mature BDNF (mBDNF) protein levels were decreased, whereas the phosphorylation of its receptor TrkB as well as of its intracellular signaling molecules Akt and ERK1 were increased. mBDNF protein expression and its signaling in cocaine-naïve serotonin transporter knockout rats resembled that of wild-type rats with a history of long-access cocaine self-administration. Interestingly, cocaine-exposed serotonin transporter knockout rats showed increased BDNF levels, with no signs of phospho-TrkB receptor coupling to phospho-Akt and phospho-ERK1. Conclusions: Long-access cocaine self-administration dysregulates BDNF signaling in the central amygdala. Vulnerability to cocaine addiction is associated with dysregulation of this signaling.